E-Banking as a Tool for Competition Advantage in Albania - Bazini, Evelina (European Journal of Economics and Business Studies, 2015)
The adoption of e-banking is occurring quite extensively as a channel of distribution for financial services due to rapid advances in ICT and intensive competitive banking markets. E-banking offers o lot of benefits which add value to customers’ satisfaction in terms of better quality of service offerings and at the same time enable the banks gain more competitive advantage over other competitors. Internet banking is either offered as a value added service of physical bank branches or a virtual bank where customers can only perform banking transactions through the Internet and it is important to mention that operating costs of a virtual bank are much lower compared to traditional banks. This study is designed to evaluate e-banking as a strategy and related methods adopted in banking sector in Albania to improve the customer satisfaction. The aim was to analyze customers’ perception towards e-banking services, the quality of e-banking services provided by the banks and the constraints in achieving customer satisfaction. The study also recommends the possible and practical additional measures the banks should take in order to achieve maximum customer satisfaction. Data were collected from the bank customers through self designed structured questionnaires. Out of 100 questionnaires distributed, only 62 percent were returned/ responded back. Non-probability sampling was used due to the limitation of resources and time. Data management and analyses were done using SPSS program and Microsoft excel.
Keywords: e-banking, competitive advantage, customers satisfaction, e-distribution channels.